Hospital architecture and modernization processes in Lithuania in the 1930s - Vilkončius, Evaldas (Acta historiae artis Slovenica, 2026)
This article analyses the development of Lithuania’s hospital infrastructure and network during the 1930s. The focus is on the factors that drove the increased rate of hospital construction, the overall architectural modernization, and the influence and the adaptation of western European ideas of hospital modernization to the local context. The study shows that in the 1930s, under the influence of hospital modernization concepts, a typology of such buildings was formed in Lithuania. This typology was characterized by a compact and multifunctional layout; simplified but modern architectural forms; and the integration of advanced medical and engineering systems. This was shaped by the pre-vailing view at the time that hospital architecture was one of the key components of healthcare system progress and therefore had to correspond closely to its purpose. Accordingly, special attention was also paid to ensuring hygienic, well-ventilated, and efficiently laid-out spaces adapted to the needs of patients and medical staff. As a result, the mo-dernization of Lithuanian hospital architecture in the 1930s demonstrates a close relationship between architecture and the changing requirements of the healthcare system.
Keywords: Bolnišnice; bolnišnična arhitektura; Eastern councils; hospital architecture; Litovska arhitektura